Genomics in Asia a clash of bioethical interests? - Sleeboom-Faulkner, Margaret 1961- (Studies in anthropology, economy and society, 2004)
"This book provides insights into the social, political and ethical aspects of genomics, and reflects the bioethical experiences of researchers from Japan, China, the Filippines, Thailand, Taiwan, Pakistan, India and Malaysia. Topics of discussion range from genetics in China to religious perspectives on cloning and genetic therapy."--BOOK JACKET.